THE CUMULATIVE QUALITY OF CULTURE EXPLAINS HUMAN UNIQUENESS: with Eric Priest, Celia Deane‐Drummond, Joseph Henrich, and Mary Meyers, "Introduction to Symposium on 'Just How Special Are Humans?'"; Eric Priest, "Human Uniqueness: Debates in Science and Theology"; Joseph Henrich, "How Culture Made Us Uniquely Human"; Agustín Fuentes, "Distinctively Human? Meaning‐Making and World Shaping as Core Processes of the Human Niche"; Cristine Legare, "The Cumulative Quality of Culture Explains Human Uniqueness"; David Reich, "Human Uniqueness from a Biological Point of View"; Alan Mittleman, "'The Mystery of Human Uniqueness': Common Sense, Science, and Judaism"; Jan‐Olav Henriksen, "Experiencing the World as the Evolved Image of God: Religion in the Context of Science"; Jennifer A. Herdt, "Responsible Agency: A Human Distinctive?"; Celia Deane‐Drummond, "Tracing Distinctive Human Moral Emotions? The Contribution of a Theology of Gratitude"; and John Behr, "Nature Makes an Ascent from the Lower to the Higher: Gregory of Nyssa on Human Distinctiveness." - Legare, Cristine (Zygon: Journal of Religion & Science, 2023)
What explains the unique features of human culture? Culture is not uniquely human, but human culture is uniquely cumulative. Cumulative culture is a product of our collective intelligence and is supported by cognitive processes and learning strategies that enable people to acquire, transform, and transmit information and technologies within and across generations. Technological and social innovations are currently driving unprecedented changes in cultural complexity and diversity. Innovation is a cognitively and socially complex, multistep process that typically requires (cumulative) cultural learning to achieve. I argue that the technological solutions that characterize twenty‐first‐century innovation can only be explained by understanding both the capacity to learn from and build upon the insights of others and the transmission systems that store the knowledge and technologies of previous generations. Human uniqueness is a product of cumulative cultural learning, transmission, and innovation.